Design and Simulation of Rectangular Microstrip Patch antenna for Wireless Communication - * Ayushi Aggarwal* Wazir, Sarika Khurana (International Journal of Scientific Research and Management (IJSRM), 2017)
This paper presents the design of microstrip patch antenna using high frequency structure simulator (HFSS 12). The two different configurations simple rectangular and dual stacked rectangular patch are designed. The performance of two antennas is analyzed in terms of bandwidth ,return loss & gain. The material used for substrate is FR4 having the dielectric constant 4.4 .This material is easily available & has low cost.The return loss of simple rectangular patch is -33.3db & gain is 4.6161db whereas the return loss for dual stacked is -30.045db & gain is 8.3313db.